2007
DOI: 10.1007/bf03160907
|View full text |Cite
|
Sign up to set email alerts
|

Limited efficacy of calcium and magnesium in a porcine model of hydrofluoric acid ingestion

Abstract: Objective: This investigation evaluated the effectiveness of calcium and magnesium in treating oral hydrofluoric acid (HF) poisoning.Methods: The controlled laboratory investigation used anesthetized pigs. Subjects received HF via NG tube, titrated to abolish electrocardiographic abnormalities. The untreated group received saline infusion. The treatment group received serial injections of calcium chloride (CaCl 2 ) and magnesium chloride (MgCl 2 ). A third group received oral infusions of Calcium fluoride (CaF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
0
19
0
2
Order By: Relevance
“…No statistically significant benefit was seen by giving either of these salts along with HF [33]. In a pig model, calcium fluoride administered orally did not lead to QRS prolongation or ventricular dysrhythmias [34]. The mechanism and efficacy of orally administered calcium and magnesium are presently unclear.…”
Section: What Is the Role For Decontamination In Hydrofluoric Acidmentioning
confidence: 97%
“…No statistically significant benefit was seen by giving either of these salts along with HF [33]. In a pig model, calcium fluoride administered orally did not lead to QRS prolongation or ventricular dysrhythmias [34]. The mechanism and efficacy of orally administered calcium and magnesium are presently unclear.…”
Section: What Is the Role For Decontamination In Hydrofluoric Acidmentioning
confidence: 97%
“…Therefore, we consider that the changes in PO 2 and PCO 2 at 30 to 120 min are attributable to respiratory compensation for metabolic acidosis. On the other hand, the BE and HCO 3 -levels did not recover from 30 to 300 min in the case of the 9.6 mg/ kg dose. As a mechanism of metabolic acidosis caused by F, it was reported that the HCO 3 -level and BE decreased owing to renal tubular acidosis 60 min after HFA administration (9.6 mg/kg) 9) .…”
Section: Discussionmentioning
confidence: 72%
“…On the other hand, the BE and HCO 3 -levels did not recover from 30 to 300 min in the case of the 9.6 mg/ kg dose. As a mechanism of metabolic acidosis caused by F, it was reported that the HCO 3 -level and BE decreased owing to renal tubular acidosis 60 min after HFA administration (9.6 mg/kg) 9) . It was also postulated that formation of fluorapatite requires dissociation of HPO 4 2-, which releases protons causing metabolic acidosis 18) .…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations